2018
DOI: 10.2139/ssrn.3237706
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Sarcoidosis Classification with Deep Convolutional Neural Network-Based Features Using Polar Maps

Abstract: Abbreviations CoV: coefficient of variation CS: cardiac sarcoidosis DCNN: deep convolutional neural network FDG: fluorodeoxyglucose JSSOG: Japanese society of sarcoidosis and other granulomatous disorders LCD: low carbohydrate diet LV: left ventricle PET: positron emission tomography SUV: standardized uptake value SVM: support vector machine 3 Abstract Aims: The aim of this study was to determine whether deep convolutional neural network (DCNN)-based features can represent the difference between cardiac sarcoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Machine learning (ML), including deep learning (DL) and ensemble learning, has been contemporarily used for the diagnosis and prognosis predictions of many eye diseases (11)(12)(13)(14). Numerous efforts have been made recently to accurately detect DME by ML based on OCT images due to continuous increase in the number of patients with DME (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning (ML), including deep learning (DL) and ensemble learning, has been contemporarily used for the diagnosis and prognosis predictions of many eye diseases (11)(12)(13)(14). Numerous efforts have been made recently to accurately detect DME by ML based on OCT images due to continuous increase in the number of patients with DME (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al developed an automated pipeline using two cascaded V-NETs for lesion prediction and segmentation to detect multiple myeloma bone lesions from 68 Ga-Pentixafor PET/CT [131]. Togo et al demonstrated the feasibility of cardiac sarcoidosis detection from 18 F-FDG PET scans using Inception-v3 network (83.9% sensitivity and 87% specificity), which outperformed conventional SUV max -(46.8% sensitivity and 71.0% specificity) and coefficient of variance (CoV)-based (65.5% sensitivity and 75.0% specificity) approaches [132]. Ma et al modified a DenseNet architecture for the diagnosis of thyroid disease using SPECT images into three categories: Graves' disease, Hashimoto, and subacute thyroiditis [133].…”
Section: Ai-assisted Diagnosis and Prognosismentioning
confidence: 99%
“…18 F-FDG PET is also a common used mean of cardiac examination and it plays a fundamental role in diagnosis of cardiac sarcoidosis (CS) (25,130). A method based on deep convolutional neural network (DCNN) was proposed for CS classification (131).…”
Section: Application Of ML In Petmentioning
confidence: 99%